ظواهر مختارة من اللهجة العمانية المعاصرة: دراسة صوتية وصرفية - البلوشي، سالم بن عبدالله بن علي (جامعة نزوى - مركز الخليل بن أحمد الفراهيدي للدراسات العربية والإنسانية, 2018)
This research reviews some of the dialectical phenomena in Oman, shows their connection with the dialects of some Arabic tribes, such as, Qais, Tamim, Al Azd, Huthail, and others, and studies phonetic differences of these dialects, such as; Linguistic Replacement, Dissimi-lation, Metathesis, Vowel Harmony, etc.... The study has relied on the analytical descriptive approach, and conclud¬ed existence of a connection between these phenomena and the dialects of some old Arab tribes. These dialects fall under specific phonetic and morphological differences confirmed by Arabic language scholars.
يعرض البحث لبعض الظواهر اللهجية في عُمان. ويبين صلتها بلغة القبائل العربية، كقيس وتميم والأزد وهذيل. وغيرها من القبائل العربية. ويعنى بالتغيرات الصوتية لهذه اللهجات، ويرجعها إلى تغيرات صوتية كالإبدال اللغوي، والمخالفة اللغوية، والقلب المكاني، والإتمام، والتوافق الحركي، وغير ذلك من الدراسات الصوتية. وقد اعتمدت الدراسة على المنهج الوصفي التحليلي. وخلصت الدراسة إلى ارتباط هذه الظواهر اللهجية المعاصرة المختارة بلهجات بعض القبائل العربية القديمة سالفة الذكر. وإنَّ هذه اللهجات تندرج ضمن تغيرات صوتية وصرفية محددة اعتمدها علماء العربية.
Keywords: اللهجة العمانية -- الظواهر اللهجية -- عمان